Association between atherosclerosis risk factors, anthropometric status and the sociodemographic factors with atherosclerosis awareness among non-covid19 patients admitted in a Teaching Hospital, Malaysia - Alati, Mohamad Ahmad (2021)
Atherosclerosis (AS), a chronic inflammatory disease, is the main cause of cardiovascular disease that entails two conditions, namely the AS risk (ASR) and disease (ASD). ASDs remained the principal cause of death worldwide yet the state of awareness of AS in hospitalised patients are not well reported. There are nutritional strategies in promoting health by understanding the detrimental effects of AS clinically but AS awareness in any individual is an essential state of mind for the healthcare provider to extend the ideal prevention or treatment program with measurable outcomes. To determine the association of atherosclerotic risk (ASR), anthropometric status and sociodemographic factors with AS awareness among non-COVID-19 patients admitted in HPUPM. This is a cross-sectional prospective study and data was obtained from respondents admitted to general medical and surgical wards in HPUPM through interviews as well as electronic medical records from October 9th, 2020 through January 1st, 2021. More than 60% were males (n=63) with more than half were ages more than 60 years old and the admission was predominantly for surgical intervention. Our research showed the prevalence of AS awareness in adult non-COVID-19 patients admitted to HPUPM was as low as 11.5% from 104 total research subjects with significant association with high cholesterol, alcohol, stress and family history but none with diabetes, insulin resistance, OSA and hypertension as per ASRs. Significant association of AS awareness are seen with BMI (p=0.0475) but not to MUAC (p=0.0622). The full blood count parameters findings were heterogenous but MCHC and RDW were within normal range in all subjects. Our research showed a worrisome low AS awareness in non-COVID19 hospitalised patients and association with BMI and certain other ASRs. Majority of the research subjects has AS and with low AS awareness therefore AS awareness is a form of ASR on its own. We recommend an AS awareness interventional program and outcome research in the future with longer follow up.